2022
DOI: 10.1037/cep0000275
|View full text |Cite
|
Sign up to set email alerts
|

Valence does not affect recognition.

Abstract: Valence refers to the extent to which a stimulus is viewed as negative or positive. One recent model of valence, the NEVER model (Bowen et al., 2018), predicts that in general negative words will be better remembered than positive or neutral words. However, this prediction is difficult to validate for recognition tests because the literature reports inconsistent findings. Three experiments reexamined whether valence affects recognition of words by taking advantage of the recent increase in the number of high-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
2
3
1
Order By: Relevance
“…We were able to replicate reports that more emotional words are better remembered regardless of polarity (i.e., extremity of valence; e.g., Adelman & Estes, 2013; Cortese & Khanna, 2022; see Phelps & Sharot, 2008), explaining 3.3% of variance. Consistent with many previous reports, valence did not significantly predict whether words were recognized or not (see MacMillan et al, 2022; cf., Bowen et al, 2018). Form typicality for valence significantly predicted memory performance, with more typical forms being better remembered, explaining an additional 1.3% of variance, while typicality for extremity of valence did not contribute significantly.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We were able to replicate reports that more emotional words are better remembered regardless of polarity (i.e., extremity of valence; e.g., Adelman & Estes, 2013; Cortese & Khanna, 2022; see Phelps & Sharot, 2008), explaining 3.3% of variance. Consistent with many previous reports, valence did not significantly predict whether words were recognized or not (see MacMillan et al, 2022; cf., Bowen et al, 2018). Form typicality for valence significantly predicted memory performance, with more typical forms being better remembered, explaining an additional 1.3% of variance, while typicality for extremity of valence did not contribute significantly.…”
Section: Discussionsupporting
confidence: 90%
“…Combined, the control variables predicted 27.8% of the variance in corrected hit probability. Of the two valence variables, only extremity of valence significantly predicted an additional 3%–3.3% of variance, with more emotional words being better remembered (see Figure 11), replicating prior work (e.g., Adelman & Estes, 2013; Cortese & Khanna, 2022; MacMillan et al, 2022). Neither valence variable interacted significantly with frequency.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…3. However, it should be noted that contrary to the prediction of the two-factor account, MacMillan et al (2022) found no difference between positive, negative, and neutral words on a recognition test.…”
Section: Declaration Of Conflicting Interestscontrasting
confidence: 88%
“…The contextual diversity and frequency manipulations affected only the false alarm rate, whereas the concreteness manipulation affected only the hit rate. Neath et al noted that of the very few articles that provide their stimuli, those that had confounded stimuli showed mirror effects (e.g., Cook et al, 2006; Glanc & Greene, 2007; Heathcote et al, 2006; Steyvers & Malmberg, 2003), whereas those that used more highly controlled stimuli did not observe a mirror effect (Macmillan et al, 2021; MacMillan et al, in press). This pattern of results suggests that mirror effects will be observed in recognition tests only when the stimuli vary systematically on two (or more) dimensions, one of which affects the hit rate (such as concreteness) and one of which affects the false alarm rate (such as frequency).…”
mentioning
confidence: 99%